Phosphoproteins in extracellular vesicles as candidate markers for breast cancer - Chen, I-Hsuan; Xue, Liang; Hsu, Chuan-Chih; Paez, Juan Sebastian Paez; Pan, Li; Andaluz, Hillary; Wendt, Michael K.; Iliuk, Anton B.; Zhu, Jian-Kang; Tao, W. Andy (Proceedings of the National Academy of Sciences - PNAS, 2017)
The state of protein phosphorylation can be a key determinant of cellular physiology such as early-stage cancer, but the development of phosphoproteins in biofluids for disease diagnosis remains elusive. Here we demonstrate a strategy to isolate and identify phosphoproteins in extracellular vesicles (EVs) from human plasma as potential markers to differentiate disease from healthy states. We identified close to 10,000 unique phosphopeptides in EVs isolated from small volumes of plasma samples. Using label-free quantitative phosphoproteomics, we identified 144 phosphoproteins in plasma EVs that are significantly higher in patients diagnosed with breast cancer compared with healthy controls. Several biomarkers were validated in individual patients using paralleled reaction monitoring for targeted quantitation. This study demonstrates that the development of phosphoproteins in plasma EV as disease biomarkers is highly feasible and may transform cancer screening and monitoring.